Studying a Two-level Supply Chain Including a Manufacturer and Several Retailers with a Wholesale Price Contract between Them - Abanavaz, Fezzeh; Bafruei, Morteza Khakzar (International Review of Management and Marketing, 2020)
As competition has intensified in today's market, most of companies have understood that their business performance is highly dependent on the degree of cooperation and coordination in the supply chain. One of the factors causing supply chain coordination is the wholesale price contract. In this study, a two-level supply chain including a producer and several retailers that wholesale price contract is established among them. First, to construct the initial model, the library method is used to make the primary model and then, mathematical methods are used to construct the model. The final goal of this study is to determine the optimum order quantity and optimal production cost and maximizes the supply chain profit in a single-period model with a random demand market. Also, the case where the exchange of goods between retailers is justified under the conditions of shortage and surplus, and retailers are co-operating with each other is also examined. Keywords: supply chain; pricing chain and order quantity; coalition of the retailers; problem of the newsvendor. JEL Classification: L1 DOI: https://doi.org/10.32479/irmm.8402